1995
DOI: 10.1136/jech.49.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in Australia: trends in socioeconomic inequalities.

Abstract: Study objective -To examine trends in socloeconomic mequalities in cardiovascular risk factors using educational attainment to indicate socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 36 publications
7
46
1
2
Order By: Relevance
“…25,26 The only known Australian study to have examined socio-economic height differentials among adults found similar trends to that reported here, namely, that SEP (educational attainment) and height were positively related for both men and women aged 25-44 and 45-64 years. 27 In this present work, average height differences between the most and least disadvantaged groups were 1.1 to 2.3 cm for males, and 1.0 to 2.5 cm for females (depending on cohor t and SEP measure). A recent Finnish study estimated that a 1 cm increase in height represented an approximately 2% reduction in mor tality, 28 thus the socio-economic height differences found in this Australian investigation possibly translate to about a 2%-5% increased mortality risk for the most disadvantaged groups.…”
Section: Discussionsupporting
confidence: 39%
“…25,26 The only known Australian study to have examined socio-economic height differentials among adults found similar trends to that reported here, namely, that SEP (educational attainment) and height were positively related for both men and women aged 25-44 and 45-64 years. 27 In this present work, average height differences between the most and least disadvantaged groups were 1.1 to 2.3 cm for males, and 1.0 to 2.5 cm for females (depending on cohor t and SEP measure). A recent Finnish study estimated that a 1 cm increase in height represented an approximately 2% reduction in mor tality, 28 thus the socio-economic height differences found in this Australian investigation possibly translate to about a 2%-5% increased mortality risk for the most disadvantaged groups.…”
Section: Discussionsupporting
confidence: 39%
“…For women, the education gradient in smoking reversed direction over time as smoking increased among the less educated, inequalities in blood pressure increased in relative but not absolute terms, and BMI inequalities increased unambiguously. In Australia, risk-factor changes in the 1980s based on physical examinations generally suggested population-wide improvements in all education groups for most risk factors, with moderate declines in inequality for blood pressure among men but not women and increasing relative inequalities for smoking and physical activity in men and for obesity in women (12). More recent estimates of self-reported data suggest that profiles of blood pressure, leisuretime physical activity, cholesterol, and smoking continue to improve, but with increases in relative inequality, whereas diabetes and obesity are increasing in all groups with narrowing relative inequalities (26).…”
Section: Wwwannualreviewsorg • Social Determinants and The Decline mentioning
confidence: 99%
“…15 Only in a few studies was no association between SES and a more consistent education gradient in women than men, for both mean systolic BP and hypertension BP found: the Princeton School District, 23 Framingham 22 and People's Gas Studies 12 and an early prevalence. 8,30,31 No change in the gradient over time was reported. An inverse association between occupational study by Lee.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 99%